ACUPUNCTURE IN TREATING HEPATIC FIBROSIS: A REVIEW WITH RECOMMENDATION FOR FUTURE STUDIES - Zhou, Jue; Liang, Yi; Lin, Xian-Ming; Ma, Rui-Jie; Fang, Jian-Qiao (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Hepatic fibrosis, as a major medical problem, is characterized with significant morbidity and mortality. Acupuncture has potential advantages in treating hepatic fibrosis as acupuncture functions well to reduce Qi and Blood stagnation, resolve stasis and enhance body immunity, which are important factors in treating hepatic fibrosis. The aim of this review was to appraise the current limited evidence of acupuncture in treating hepatic fibrosis from both animal experiments and clinical trials by using both Chinese and western databases and to provide recommendations for future studies.